A marca Usain Bolt: contratos de comunicação de uma Me Brand em midiatização - Hönig, Rafael dos Santos (2020)
The following study seeks to understand the communication contracts used by sprinter Usain Bolt throughout different moments of his career, which aimed to build his brand in a context of mediatization of society. On the rise in recent years, Me Brands are symbolic compositions manifested in the sensitive sphere from the subject's bodily dispositions, which are oriented according to logics of prominence, influence and/or monetization. In order to reflect on these brands, this work is divided into four chapters. The first argues that the brand could arise, initially, from potentialities offered by the symbolic nature of being; presents considerations on the attribution of representations to materialities; deals with the indicative singularity of the body, which expresses itself with antagonisms; and debate about timely insertions and the need for a communication contract. The second chapter presents some contributions of the mediatization process for the strengthening of brands in contemporary times. Studies by different authors are articulated to discuss the context of the transformation of society; a topic is dedicated to the impact of mediatization on the reality of brands; another includes a brief survey on concepts related to subject brands in academia and the marketing field, as well as a justification for choosing the term Me Brand. The third chapter explains the stages of identification and selection of the corpus based on the indicative paradigm proposed by Braga (2008), which is inspired by Ginzburg (1999) and Sebeok and Umiker-Sebeok (2004). For the analysis, Charaudeau's communication contract (2018) guides the view of the sprinter's attitudes in moments before, during and after competitions in international events. Finally, the last chapter presents a return to the path constructed in the dissertation and elaborates some inferences for future researches. It appears that Bolt, when proposing different communication contracts, not only defines the recipients, but also encourages the circulation of subjects and interests, further strengthening his brand. In addition, it encourages those involved in the communication process to act according to their contract, as it leaves latent some approaches, in terms of behavioral regularities and ways of saying, that others may have. As a brand, it is able to indirectly modify the production and consumption of media events in which it is present.